Single crystal characteristics of the Mg - 5% Li alloy, found from the polycrystalline experimental data and the Kearns texture parameters - Usov, V.; Shkatulyak, N.; Sovkova, T.; Rybak, N. (Physics and Chemistry of Solid State, 2022)
This work aimed to experimentally determine of the Kearns texture parameters, elastic moduli, mechanical properties (ultimate tensile strength and yield strength) of sheets of an alloy of Mg 5 wt. % Li after various types of processing: 1) extrusion at 350 ° C through a rectangular die; 2) rolling with a change in its direction by 90° and intermediate annealing at 350°C after each pass; 3) after the subsequent alternating bending (AB) by 0.5; one; 3 and 5 cycles and evaluation of the elastic and mechanical properties of the corresponding single crystal of the alloy under study using the indicated data. The moduli of elasticity and strength characteristics of the studied polycrystalline samples were determined in the rolling direction (RD) and transverse direction (TD). Using the found parameters of the Kearns texture and the elastic and mechanical properties of the sheets, the values of the elastic modules and the ultimate strength and yield strength of the single crystal of the above alloy were estimated. The found modules of elasticity of a single crystal of an alloy Mg-5 wt. % Li deviate from their values found in previous studies by no more than 7.5%. Elastic modules and strength characteristics of the studied samples of magnesium alloy Mg 5 wt. % Li calculated from the single crystal data deviate from the experimental data by no more than 10%.